Protecting Women from Domestic Violence: Islam, Family Law, and the State in Indonesia - Alfitri, Alfitri (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2020)
Despite the enactment of a specific law on domestic violence, the elimination of violence in the household is still an elusive target in Indonesia. For example, according to the National Commission on Anti Violence Against Women, a large number of Muslim divorces in the Religious Courts have involved domestic violence. This article discusses the opportunities and challenges for eliminating domestic violence in Indonesian Muslim society. Employing both normative and socio-legal analysis, it finds that the state is unable to resolve the existing conflict between the requirements of the Law – which oblige the state to amend conflicting legislation – and the provisions of both civil and Islamic marriage laws, which create the potential for violence against women in the household. These include gender role stereotypes, the fuzziness of the obedience concept (nushūz) and linking maintenance to a wife’s obedience, and the ambiguity of marriage validity. This necessitates the reformation of Indonesian marriage laws.